Immunobiotics: Interactions of Beneficial Microbes with the Immune System - Haruki Kitazawa (Frontiers Research Topics, 2018)
The term "immunobiotics" has been proposed to define microbial strains able to beneficially regulate the mucosal immune system. Research in immunobiotics has significantly evolved as researchers employed cutting-edge technologies to investigate the complex interactions of these beneficial microorganisms with the immune system. During the last decade, our understanding of immunobiotics-host interaction was profoundly transformed by the discovery of microbial molecules and host receptors involved in the modulation of gut associated immune system, as well as the systemic and distant mucosal immune systems. In recent years, there has been a substantial increase in the number of reports describing the beneficial effects of immunobiotics in diseases such as intestinal and respiratory infections, allergy, inflammatory bowel disease, obesity, immunosuppression, and several other immune-mediated conditions. Evidence is also emerging of immunobiotics related molecules with immunomodulatory functions leading to the production of pharmabiotics, which may positively influence human or animal health. Therefore, research in immunobiotics continue to contribute not only to food but also medical and pharmaceutical fields. The compilation of research articles included in this ebook should help reader to have an overview of the recent advances in immunobiotics.